Protective Roles of N-trans-feruloyltyramine Against Scopolamine-Induced Cholinergic Dysfunction on Cortex and Hippocampus of Rat Brains - Thangnipon, Wipawan; Ngampramuan, Sukonthar; Suthprasertporn, Nopparat; Jantrachotechatchawan, Chanati; Tuchinda, Patoomratana; Nobsathian, Saksit (Siriraj Medical Journal, 2021)
Objective: To study the protective effects of N-trans-feruloyltyramine (NTF) on scopolamine-induced cholinergic dysfunction, apoptosis, and inflammation in rat brains. Materials and Methods: Treatments were administered intraperitoneally (i.p.). Wistar rats (8-week-old) were allocated into 4 groups (n = 3) as follows: scopolamine-only, NTF-only, NTF + scopolamine and control. Spatial cognition was evaluated by Morris water maze. ROS assay and Western blot analyses were conducted in 3 brain regions: the frontal cortex, hippocampus, and temporal cortex. Results: NTF treatment inhibited scopolamine-induced memory impairment and significantly attenuated scopolamine-induced changes in the three brain regions. Investigated scopolamine-associated changes were as follows: increases in ROS production and BACE1 level, decrease in ChAT level, increases in inflammatory and apoptotic markers, and activation of signaling pathway kinases related to inflammation and apoptosis. Conclusion: With its in vivo antioxidant, cholinergic-promoting, anti-apoptosis, and anti-inflammatory biological activities, NTF is a promising candidate to be further investigated as a potential treatment for Alzheimer’s-associated neurodegeneration.